Healthcare professionals' knowledge, attitude and its associated factors toward electronic personal health record system in a resource-limited setting: A cross-sectional study - Wubante, Sisay Maru; Tegegne, Masresha Derese; Melaku, Mequannent Sharew; Mengiste, Nebyu Demeke; Fentahun, Ashenafi; Zemene, Wondosen; Fikadie, Makida; Musie, Basazinew; Keleb, Derso; Bewoketu, Habtemaryam; Adem, Seid; Esubalew, Simegne; et al. (Frontiers in Public Health, 2023)
Introduction: - Electronic personal health records system enables individuals can access their health information and manage it by themselves. It helps patient engagement management of health information that is accessed and shared with their health care providers using the platform. This improves individual health care through the exchange of health information between patients and healthcare providers. However, less is known about Electronic personal health records among health professionals Objective:-Therefore, this study aimed to assess electronic personal health record knowledge and attitude and its associated factors among health Professionals at the teaching Hospital North West Ethiopia. Methods: An institution-based cross-sectional study design was employed to determine health professionals’ knowledge and attitude toward electronic personal health record systems and its associated factors inteaching hospitals of Amhara regional state, Ethiopia from July 20 to August 20, 2022. Pretested structured self-administered questionnaires were employed to collect the data. Descriptive statistic was computed on socio-demographic and other variables presented in the form of table graphs and text. Bi-variable and multivariable logistic analysis was done with an adjusted odd ratio and 95%CI to identify predictor variables. Result: from the total study participants 57% were males and nearly half of the respondents had a bachelor's degree. Out of 402 participants, about 65.7%[61%-70%]and 55.5%[50%-60%] had good knowledge and favorable attitude toward electronic personal health record systems respectively. Having social media account 4.3[AOR=4.3,95% CI(2.3-7.9)], Having Smartphone 4.4[AOR=4.4,95% C I(2.2-8.6)] ,Digital literacy 8.8[(AOR=8.8,95% CI(4.6-15.9)],Being male2.7[AOR=2.7,95% CI(1.4-5.0)]Perceived usefulness 4.5[(AOR=4.5,95% CI(2.5-8.5)] were positively associated on knowledge towards electronic personal health record system.Likewise, having personal computer 1.9 [AOR=1.9,95% CI(1.1-3.5))],Computer training3.9 [AOR=3.9,95% C I(1.8-8.3)],computer skill 19.8 [AOR=19.8,95% CI(10.7-36.9)],Internet access 6.0 [AOR=6.0,95%CI(3.0-12.0)] were predictors for attitude towards electronic personal health record system. Conclusion: The findings from the study showed that health professionals have good knowledge and a favorable attitude towards e-PHRs respectively. Capacity building of health professionals through digital literacy and computer skills has a paramount contribution to the advancement of their understanding and positive influence on electronic personal health record systems.